Enhanced Piezoelectric Coefficient of PVDF-TrFE Films via In Situ Polarization - Hu, Xiaoran; You, Mengli; Yi, Na; Zhang, Xiaokun; Xiang, Yong (Frontiers in Energy Research, 2021)
The 10X times of d33 coefficient of PVDF-TrFE piezoelectric films were achieved by the in-situ polarization. Compared with traditional polar methods, the in-situ polarization was performed with low poling voltage, short poling time, and can ensure the obtained PVDF-TrFE film with enhanced piezoelectric performances and uniform distribution among large area of 200 × 200 mm2. The processing influence of drying, annealing and poling on the crystalline properties and piezoelectric performances were investigated. Besides, the obtained PVDF-TrFE films present good piezoelectric response to different extent of mechanical stimulations, which has great potential in energy harvesting applications.